CONTEMPORARY INDIAN WOMEN ARTISTS AS DIGITAL SOCIAL COMMENTATORS ON WOMEN'S EMPOWERMENT - Dayal, Deepanjali; Chauhan, Rajesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In recent years, there has been a rapid increase in the number of Indian women artists harnessing digital platforms to critique and engage with societal norms surrounding gender equality and women’s empowerment. Being active participants on digital platforms they are strongly addressing issues related to women’s rights by socially commentating through their art. Digital platforms encourage global audiences and international access to artworks that enable artists to amplify their content through active social media engagement. Social media platforms are powerful mediums of connection that encourage the boosting of young talent to reach diverse audiences through their exhilarating art pieces. These women artists are presenting themselves and letting out their voice through art campaigns, projects, series, installations, 3D artworks, crypto, digital paintings, etc. to bring to the forefront topics such as gender bias, patriarchy, violence against females, stereotyping, inclusivity, sexuality, consent, body shaming, feminine perfection, female beauty standards and so on. They are motivated to present to the women of India, the need to be aware of the challenges and threats imposed on their identity as the society in which they live is at the turn of acknowledging a new age that is ready to offer acceptance and equality to women on the terms of their fight and struggle of pushing the system forward from the dead asleep. The digital artworks of a senior contemporary women artist and a young digital social commentator will be discussed in the paper to present a richer and more comprehensive understanding of the socio-political issues addressed through the artistic journey of these two artists belonging to different age groups.